PENGARUH KUALITAS PRODUK, HARGA, PROMOSI DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK METRO MEDIA LOMBOK (Studi Kasus Pada Pelanggan Metro Media Lombok Di Lombok) - Muhamad Yuma Meidiansyah; N. Rachma; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis research was conducted to determine the effect of product quality, price, promotion and service quality on purchasing decisions for Metro Media Lombok products. Which is located at Jl. TGH. Ibrahim Khalidy Kec. Labu Api District West Lombok. The method used is explanatory research which aims to explain the position of each variable and its influence between one variable with another variable, and the source of the data used is primary data by distributing linkie-scale kusieoner to consumers of Metro Media Lombok stores. The sample calculation in this study uses the maholtra formula which produces 145 respondents. The results of this study are the variables of product quality, price, promotion and service quality simultaneously or partially influencing the purchase decision.Keywords: product quality, price, promotion, service quality and purchasing decisions.